Entrepreneurial Educational Ecosystem in Morocco: An Exploratory Study - Malak EL BOURY; Ahlam QAFAS (Communications of International Proceedings, 2021)
The Global Entrepreneurship Monitor - an international entrepreneurship indicator - considers entrepreneurship education as one of the 9 framework conditions for the evolution of entrepreneurship. Therefore, the development of the entrepreneurial educational ecosystem is believed to influence cultural values and to foster the economic development of a nation. For this reason, the question is: how education can foster entrepreneurship in Morocco? Hence, this paper aims firstly to present some theoretical guidelines on entrepreneurship education; and then through semi-structured interviews, to explore the current state of entrepreneurship in Morocco and the training needed to improve the entrepreneurial educational ecosystem from the perspective of Moroccan entrepreneurs.
Keywords: Education Ecosystem; Entrepreneurship; Exploration; Semi-structured interviews